La gamificación en ambientes de aprendizaje para la enseñanza del bilingüismo, avances teóricos, metodológicos y tendencias en la investigación: una revisión sistemática 2018-2023 - Lisbeth Carolina Reyes Afanador; Micke Annderson Cubillos Leal; Zulmary Carolina Nieto Sánchez; José Alberto Cristancho; Lucy Thamara Useche Cogollo (Mundo Fesc)
Gamification has been studied and used in recent years for teaching in various primary and secondary educational contexts, including at the university and business levels. The purpose of this article is to conduct a systematic review based on research conducted between 2018 and 2023, seeking to establish theoretical and methodological advances, trends, and contributions regarding gamification in learning environments for teaching bilingualism. It highlights the latest trends in the theories used in gamification, as well as the methodologies most commonly implemented by the authors. These contribute to providing new opportunities for implementing gamification in teaching-learning models and methods, enabling institutional strengthening by incorporating play and technology as a means of teaching a second language.